Answer:
Step-by-step explanation:
Supplementary angles add up to 180
∠1 + 50 = 180
∠1 = 180 - 50
∠1 = 130
∠3 +50 = 180 {Supplementary}
∠3 = 180 - 50
∠3 =130
⇒∠1 = ∠3 = 130
The vertex of this parabola is at (3,-2). When the x-value is 4, the y-value is 3: (4,3) is a point on the parabola. Let's use the standard equation of a parabola in vertex form:
y-k = a(x-h)^2, where (h,k) is the vertex (here (3,-2)) and (x,y): (4,3) is another point on the parabola. Since (3,-2) is the lowest point of the parabola, and (4,3) is thus higher up, we know that the parabola opens up.
Substituting the given info into the equation y-k = a(x-h)^2, we get:
3-[-2] = a(4-3)^2, or 5 = a(1)^2. Thus, a = 5, and the equation of the parabola is
y+2 = 5(x-3)^2 The coefficient of the x^2 term is thus 5.
If 3% out of 100% are defective it would be 3 out of every 100, and 3 multiplied by 5 is 15. Then you multiply 100 by 5 and its 500 so out of 500 parts 15 would be defective
By using the definition of inverse functions, we will see that:
g(g(f(f(f(36))))) = f(36) = 25.
<h3>
What are inverse functions?</h3>
Two functions f(x) and g(x) are inverses if:
f( g(x) ) = x
g( f(x) ) = x
Then we can rewrite:
g(g(f(f(f(36)))))
First, we can see that:
g(f(f(f(36)))) = f(f(36))
Replacing that in our expression, we get:
g(g(f(f(f36))))) = g(f(f(36)))
And the above expression is equal to f(36), to be sure of that, let's replace:
u = f(36)
Then we can rewrite:
g(f(f(36))) = g(f(u))
And by definition, the above thing is equal to u:
g(f(u)) = u = f(36).
Finally, we conclude that:
g(g(f(f(f(36))))) = f(36) = 3*√36 + 7 = 3*6 + 7 = 25
If you want to learn more about inverse functions, you can read:
brainly.com/question/12220962